Impact of high-risk and low-risk human papillomavirus infections on the male genital tract: effects on semen inflammation and sperm quality - Olivera, Carolina; Paira, Daniela A.; Olmedo, Andrés; Olmedo, José J.; Tissera, Andrea D.; Molina, Rosa I.; Motrich, Rubén D.; Cuffini, Cecilia G.; Rivero, Virginia E. (Frontiers in Cellular and Infection Microbiology, 2024)
Human Papillomavirus (HPV), a prevalent sexually transmitted infection, comprises high-risk (HR-HPV) and low-risk (LR-HPV) viruses, the former posing a high risk for developing malignancies whereas the latter mainly for benign warts. Despite increasing awareness of HPV’s impact on men’s health, the influence of HR-HPV and LR-HPV urogenital infections on male fertility potential remains uncertain. This study aimed to investigate whether male urogenital infection with HR- or LR-HPV associates with impaired sperm quality, oxidative stress, and inflammation. A total of 205 male patients attending an urology clinic were enrolled. Semen samples were analyzed for HPV using PCR and genotyped by RFLP. Semen quality was evaluated following WHO guidelines. Semen leukocytes, reactive oxygen species (ROS), and sperm viability were analyzed using flow cytometry. HPV was detected in 19% (39/205) of semen samples. HR-HPV infections were more prevalent, with HPV-16 being the most frequent genotype. Neither HR-HPV nor LR-HPV were associated with significant alterations in routine sperm quality parameters. However, HR-HPV+ individuals showed significantly higher levels of sperm necrosis and exhibited increased proportions of ROS+ spermatozoa compared to LR-HPV+ or control individuals. Furthermore, no significant semen inflammation was detected in patients infected with either HR-HPV or LR-HPV, and unexpectedly reduced semen leukocytes and inflammatory cytokines (IL-6 and IL-1β) were observed in HR-HPV+ patients compared to controls. These observations underscore the importance of comprehensive HPV screening, including genotyping, in urology and fertility clinics to understand the progression of the infection, potential adverse effects on reproductive health, and the oncogenic risks involved.